2015
DOI: 10.1007/s13311-015-0357-7
|View full text |Cite
|
Sign up to set email alerts
|

Autism-Like Behavior in BTBR Mice Is Improved by Electroconvulsive Therapy

Abstract: Autism is a developmental disorder characterized by impairments in social and communication abilities, as well as by restricted and repetitive behaviors. Incidence of autism is higher than earlier estimates, and treatments have limited efficacy and are costly. Limited clinical and experimental evidence suggest that patients with autism may benefit from electroconvulsive therapy (ECT). We examined the therapeutic potential of ECT in BTBR T+ tf/j mice, which represent a validated model of autism. A series of 13 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Consistent with this hypothesis, Viaat-Mecp2 À /y mice have reduced GABA in the striatum (Chao et al, 2010) which could contribute to their stereotypies and which might be restored by ECS. Finally, Hagen et al (2015) recently reported response of another autism-like mouse model demonstrating excessive selfgrooming, BTBR mice, to ECS, although they required multiple ECS sessions to suppress self-grooming. One possible explanation for why the Viaat-Mecp2 À /y mice were sensitive to just one ECS in our hands is that we used a pulse width of 0.9 ms compared with a pulse width of 0.1 ms used by Hagen and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this hypothesis, Viaat-Mecp2 À /y mice have reduced GABA in the striatum (Chao et al, 2010) which could contribute to their stereotypies and which might be restored by ECS. Finally, Hagen et al (2015) recently reported response of another autism-like mouse model demonstrating excessive selfgrooming, BTBR mice, to ECS, although they required multiple ECS sessions to suppress self-grooming. One possible explanation for why the Viaat-Mecp2 À /y mice were sensitive to just one ECS in our hands is that we used a pulse width of 0.9 ms compared with a pulse width of 0.1 ms used by Hagen and colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…This unexpected lack of effect could be due to the elevated baseline plasma oxytocin levels observed in BTBR mice (Silverman et al 2010 b). An oxytocin receptor blocker, L368,899, was effective at reversing the increase in social approach (but not in social novelty preference or the reduction in grooming) caused by electroconvulsive therapy in BTBR mice (Hagen et al 2015). Another possibility is that chronic intranasal administration is not a suitable method for oxytocin supplementation for mice.…”
Section: Molecular Mechanismsmentioning
confidence: 99%
“…The BTBR model has been used to study potential new therapeutic targets, such as (i) the peroxisome proliferator activated receptor—alfa (PPAR-a), which can be stimulated by the drug risperidone, decreasing repetitive behavior in BTBR animals [ 39 ], (ii) new forms of treatment for ASD, such as electroconvulsive therapy [ 40 ], and (iii) the effect of new drugs, like methyl-6-(phenylethynyl)-pyridine (MPEP) [ 41 ]. Also, environmental factors have been investigated with the BTBR model, such as (i) high-fat diet, which was found to exacerbate the cognitive rigidity and social deficits of the BTBR mouse [ 42 ], and (ii) organophosphate insecticides, which cause developmental neurotoxicity at subtoxic doses, showing a potential for aggravating the motor patterns of neonatal mice.…”
Section: Pre-clinical Research: Inflammation In Animal Models Of Asd mentioning
confidence: 99%
“…SHANK3 protein is expressed in cortex and hippocampus and contributes to synaptic development [ 173 ]. Similarly to humans, SHANK3 has been identified in genetic mice models of ASD [ 40 ], as highlighted in Section 2.1.1. Functionally, miR-7 overexpression decreased the density of dendritic spines in a SHANK3-dependent manner [ 40 , 174 ].…”
Section: Clinical Research: Inflammatory Cells and Biomarkers In Asd mentioning
confidence: 99%
See 1 more Smart Citation